A Prospective Multi-Center Observational Trial to Evaluate a CMV-specific ELIspot Assay in Solid Organ Transplant (SOT) Recipients: The PROTECT Study. (July 2018) - Kumar, Deepali; Chin-Hong, Peter; Kayler, Liise; Wojciechowski, David; Limaye, Ajit P; Gaber, Osama; Ball, Simon; Mehta, Aneesh; Blanchard, Ted `; Kotton, Camille
Abstract : Introduction: CMV replication in transplant recipients is primarily controlled by the T-cell response. We evaluated the role of a novel CMV-specific ELISPOT assay to predict protection against CMV infection in SOT recipients. Materials and Methods: This was a multi-center (43 sites), prospective, observational study of kidney transplant recipients at risk for CMV. Subjects were enrolled either pre-transplant or during initial anti-viral prophylaxis. Clinical management was performed according to local institutional protocols. Cell-mediated immunity (CMI) was determined using an ELISPOT assay that evaluated responses to CMV-specific antigens IE-1 and pp65, from the capture of IFN-γ enumerated as spot counts (T-SPOT.CMV, Oxford Immunotec). CMV CMI and quantitative PCR (Roche Cobas) were assessed at 1, 2, 3, 4 and 6 months following completion of anti-viral prophylaxis. CMV events necessitated a change in anti-viral therapy or immunotherapy to be eligible for analysis. The endpoint was the first occurrence of CMV disease or CMV infection after the completion of prophylaxis. T-SPOT values taken at the completion of prophylaxis were analyzed to predict protection against CMV up to 1 year post-transplant. Results: Of the 597 subjects enrolled, 411 were included in the analysis based on having valid TSPOT counts within ± 30 days of the completion of prophylaxis and a non-missing date of completion of prophylaxis. Of the 411 subjects, 203 were R+ (49%), 178 were D+/R- (43%), 22 were D-/R- (5%) and 8 subjects had unknown CMV serostatus. The majority of patients were white (67%), male (62%), and median age was 52. Most patients received 3 months of antiviral prophylaxis (55%) vs 6 months of prophylaxis (44%). 3 subjects did not receive any antiviral prophylaxis (1%). Of the 411 eligible subjects, 87 had an IE-1 response of > 50 spots at the completion of prophylaxis. In this group, 1 of 87 developed CMV infection following the completion of prophylaxis, resulting in a negative predictive value (NPV) against the occurrence of a CMV event of 98.9% (p=0.0014) (see Figure 1). Using the same cut-off for pp65, the NPV against the occurrence of a CMV event was 96.5% (p=<0.0001) (see Figure 2). Figure. No caption available. Figure. No caption available. Conclusion: To date, this is the largest prospective study on the use of IFN-γ release assays to predict the risk of CMV infection in organ transplant recipients. We show that T-SPOT.CMV IE-1 and pp65 spot counts > 50 at the completion of prophylaxis are a significant predictor of protection against CMV infection/disease in SOT recipients.